How Business Intelligence Enhance The Performance of Academic Staff? - Al-maaitah, Tamara Adel; Al-maaitah, Dirar Abdelaziz (Journal of Posthumanism, 2025)
The Excution of of Business Intelligence (BI) in Jordan has seen swift growth parallel to global tech progress and the government's effort to digitalize the nation's economy. As technology progresses, BI keeps evolving and is more frequently utilized, particularly within the education sector, to enhance the teaching and learning experience. The objective of this research is to investigate University college’s Academic staff' comprehension and Excution of of Business Intelligence (BI) in classroom instruction and learning. Nonetheless, the extent of comprehension and Excution of of Business Intelligence (BI) by University college’s educators remains inadequately understood. This research employed a quantitative method as its design. A total of 100 University college’s educators in Jordan, were chosen randomly to be the sample for the study. A series of probing questions served as a tool to assess the degree of comprehension and Excution of of Business Intelligence (BI) in the teaching and learning practices of University college’s educators in the Jordan. The gathered data were tested with the Statistical Package for Social Science (SPSS) software, utilizing both descriptive statistics and inferential analysis. The research results indicate that most University college’s educators in the examined area possess a basic level of comprehension, even though they exhibit a strong interest in utilizing Business Intelligence (BI) in education. Although there is significant enthusiasm for AI integration, various obstacles persist such as inadequate training, scarce resources, and worries about BI's effect on Academic staff' roles. This research objectives to aid in enhancing the quality of University college’s education in Jordan by utilizing modern technology.